THE INFLUENCE OF SOIL CROPS AND MINERAL FERTILIZER RATE ON CHANGES IN SOIL SALINITY INDICATORS - Khalikov Bakhodir Meylikovich; Ganiev Sanjar Ernazarovich (Journals Park Publishing, 2025)
This article presents the results of a scientific study on the effect of siderate crops and mineral fertilizers on soil salinity in the conditions of moderately saline pasture-growing gray soils of the Jizzakh region in different proportions and rates. According to it, in these conditions, the use of rapeseed and perco crops as siderates or the application of manure at a rate of 10 and 20 t/ha in addition to mineral fertilizers serves to maintain the amount of agronomically active salinity in the soil.
Keywords: pasture-growing gray soils, salinity, rate, siderate crops, manure, mineral fertilizer rates.